1981
DOI: 10.1017/s1446788700019467
|View full text |Cite
|
Sign up to set email alerts
|

Regular Rees matrix semigroups and regular Dubreil-Jacotin semigroups

Abstract: A partially ordered semigroup S is said to be a Dubreil-Jacotin semigroup if there is an isotone homomorphism 9 of S onto a partially ordered group such that {x e S: xty < x9) has a greatest member. In this paper we investigate the structure of regular Dubreil-Jacotin semigroups in which the imposed partial order extends the natural partial order on the idempotents. The main tool used is a local structure theorem which is introduced in Section 2. This local structure theorem applies to many other contexts as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 9 publications
0
53
0
Order By: Relevance
“…However, the set of regular elements forms a (regular) subsemigroup. This crucial observation is due to McAlister [15]. The subsemigroup Reg(.M(/, 5, A; P)) is usually denoted UM(I, S,A;P) and is called the / x A regular Rees matrix semigroup over S with sandwich matrix P. Regular Rees matrix semigroups over inverse semigroups are of special importance (see [15,16] …”
Section: Preliminariesmentioning
confidence: 99%
“…However, the set of regular elements forms a (regular) subsemigroup. This crucial observation is due to McAlister [15]. The subsemigroup Reg(.M(/, 5, A; P)) is usually denoted UM(I, S,A;P) and is called the / x A regular Rees matrix semigroup over S with sandwich matrix P. Regular Rees matrix semigroups over inverse semigroups are of special importance (see [15,16] …”
Section: Preliminariesmentioning
confidence: 99%
“…McAlister [23] showed that if S is a regular semigroup then the regular elements of M(I, S, Λ, P ) form a subsemigroup, which he called a regular Rees matrix semigroup and denoted RM(I, S, Λ, P ). We prefer the notation Reg M(I, S, Λ, P ).…”
Section: Semidirect Products Of Regular Semigroups 4283mentioning
confidence: 99%
“…To show that S contains a subsemigroup isomorphic to Sp 4 it suffices by Lemma 3.1 to show that 91L does. The maximum idempotent-separating congruence n on eSe induces an idempotent-separating homomorphism from L(eSe; m, m; P) into 91L(e5e/ju; m, m; P^) where for P = (/?, 7 ) we denote by Pl^ the matrix (p^fi*). Let £ = £ eS< ,.…”
Section: Let S Be a Non-completely Simple Bisimple Semigroup Which Ismentioning
confidence: 99%